X-chromosome Short Tandem Repeats Resolved Complex Kinship Cases in Malaysia: Case Reports - Aedrianee Reeza Alwi; Nor Arina Syafawati Abd Aziz; Nur Hafiza Md Yusop; Wan Nur Zawani Wan Mohd Samsuddin; Faezah Mohd Salleh; Seri Mirianti Ishar; Mohd Radzniwan A. Rashid; Sharifah Nany Rahayu Karmilla Syed Hassan (Universiti Putra Malaysia, 2026)
Indexed by Scopus/MyCite